Medical students' online learning technology needs. (February 2014) - Han, Heeyoung; Nelson, Erica; Wetter, Nathan
Summary Purpose This study investigated medical students' online learning technology needs at a medical school. The study aimed to provide evidence‐based guidance for technology selection and online learning design in medical education. Methods The authors developed a 120‐item survey in collaboration with the New Technology in Medical Education (NTIME) committee at the Southern Illinois University School of Medicine (SIUSOM). Overall, 123 of 290 medical students (42%) at the medical school participated in the survey. The survey focused on five major areas: students' hardware and software use; perception of educational technology (ET) in general; online behaviours; perception of ET use at the school; and demographic information. Results Students perceived multimedia tools, scheduling tools, communication tools, collaborative authoring tools, learning management systems and electronic health records useful educational technologies for their learning. They did not consider social networking tools useful for their learning, despite their frequent use. Third‐year students were less satisfied with current technology integration in the curriculum, information sharing and collaborative learning than other years. Students in clerkships perceived mobile devices as useful for their learning. Students using a mobile device (i.e. a smartphone) go online, text message, visit social networking sites and are online during classes more frequently than non‐users. Conclusions Medical students' ET needs differ between preclinical and clinical years. Technology supporting ubiquitous mobile learning and health information technology (HIT) systems at hospitals and out‐patient clinics can be integrated into clerkship curricula.